A review of the efficiency of the JSE Securities Exchange - Wood, Adrian Michael (My University, 2011)
The ability of stock markets to function and operate efficiently has long been a question posed by academics and investors alike. In an efficient market, all information is reflected within share prices and therefore leaves no chance for economically viable arbitrage opportunities. Although this notion has been supported by the Efficient Market Hypothesis, it has come under scrutiny over the last three decades. This report has attempted to establish the extent to which the JSE Securities Exchange is an efficient market, based on the outcomes of previous empirical studies done from 1974 and 2006. Using the Historical Research Methodology, it has been found that overall the JSE Securities Exchange operates as an efficient market, in all forms of the Efficient Market Hypothesis. Along with this conclusion however, is an indication that the market also show signs of inefficiencies for certain stock types, which may have been exploited by shrewd investors
MBA - WBS
Keywords: Johannesburg Securities Exchange